The LisbOn KInetics Boltzmann solver. (10th April 2019) - Tejero-del-Caz, A; Guerra, V; Gonçalves, D; da Silva, M Lino; Marques, L; Pinhão, N; Pintassilgo, C D; Alves, L L
Abstract: The LisbOn KInetics Boltzmann (LoKI-B) is an open-source simulation tool (https://github.com/IST-Lisbon/LoKI ) that solves a time and space independent form of the two-term electron Boltzmann equation, for non-magnetised non-equilibrium low-temperature plasmas excited by DC/HF electric fields from different gases or gas mixtures. LoKI-B was developed as a response to the need of having an electron Boltzmann solver easily addressing the simulation of the electron kinetics in any complex gas mixture (of atomic/molecular species), describing first and second-kind electron collisions with any target state (electronic, vibrational and rotational), characterized by any user-prescribed population. LoKI-B includes electron-electron collisions, it handles rotational collisions adopting either a discrete formulation or a more convenient continuous approximation, and it accounts for variations in the number of electrons due to non-conservative events by assuming growth models for the electron density. On input, LoKI-B defines the operating work conditions, the distribution of populations for the electronic, vibrational and rotational levels of the atomic/molecular gases considered, and the relevant sets of electron-scattering cross sections obtained from the open-access website LXCat (http://lxcat.net/ ). On output, it yields the isotropic and the anisotropic parts of the electron distribution function (the former usually termed the electron energy distribution function ), the electron swarm parameters, and the electron power absorbed from the electric field and transferred to the different collisional channels. LoKI-B is developed with flexible and upgradable object-oriented programming under MATLAB ®, to benefit from its matrix-based architecture, adopting an ontology that privileges the separation between tool and data. This topical review presents LoKI-B and gives examples of results obtained for different model and real gases, verifying the tool against analytical solutions, benchmarking it against numerical calculations, and validating the output by comparison with available measurements of swarm parameters.